2002
DOI: 10.1023/a:1014875215580
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Responses to drought and salinity in barley (Hordeum vulgare L. cv. Tokak) were monitored by microarray hybridization of 1463 DNA elements derived from cDNA libraries of 6 and 10 h drought-stressed plants. Functional identities indicated that many cDNAs in these libraries were associated with drought stress. About 38% of the transcripts were novel and functionally unknown. Hybridization experiments were analyzed for drought- and salinity-regulated sequences, with significant changes defined as a deviation from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
101
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(113 citation statements)
references
References 40 publications
10
101
1
1
Order By: Relevance
“…Based on microarray analysis on wheat (Mohammadi et al, 2007), actin binding protein was the most highly induced transcript detected in stressed roots. In contrast, the expression of this protein in barley under drought stress was up-regulated in roots but not in leaves (Oztur et al, 2002). Therefore our observations showed that tissue specific regulation occurs at protein level.…”
Section: Osmoprotectantcontrasting
confidence: 49%
“…Based on microarray analysis on wheat (Mohammadi et al, 2007), actin binding protein was the most highly induced transcript detected in stressed roots. In contrast, the expression of this protein in barley under drought stress was up-regulated in roots but not in leaves (Oztur et al, 2002). Therefore our observations showed that tissue specific regulation occurs at protein level.…”
Section: Osmoprotectantcontrasting
confidence: 49%
“…In addition to stomatal closure, we found genes involved in photosynthetic light reaction were severely dampened during drought stress and our results are in agreement with similar findings in rice 53,62 and barley. 63,64 In root and shoot, five DEGs encoding transcription factors such as NAC012, NAC002, and NAC043 involved in developmental process 65 were upregulated while two of them are continuously upregulated (co-up) ( Table 2). NAC transcription factors are reported to impart drought stress tolerance by triggering a cascade of signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular and cellular processes underlying the acclimation of higher plants to abiotic stresses have attracted much interest, as environmental stress conditions result in the seriously loss of crop production in many parts of the world [3,4]. Using molecular and genetic approaches, a large and increasing number of genes induced by abiotic stresses have been identified recently [3,[5][6][7][8][9]. In addition, signal transduction pathways and cellular events that occur under such unfavorable growth conditions have been widely documented [10][11][12].…”
Section: Introductionmentioning
confidence: 99%